Smart Regulation For Resolving Administrative Disputes Within The Digital Public Service Ecosystem - Rafiq Pradana Wicaksono; Tessa Andini Prameswari (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2026)
The digitalization of public services in Indonesia is a major step towards efficiency, but it has also led to administrative misunderstandings, caused by system errors, data inconsistencies, algorithmic bias, and non-transparent automated decisions. Existing regulations still rely on manual procedures and have not yet addressed issues related to digital data verification, algorithmic accountability, and digital objection mechanisms. The goal of this research is to develop adaptive, data-driven smart regulations that cater to the specific characteristics of digital disputes. By means of a doctrinal sociolegal qualitative approach and through an analysis of 15 national regulations, 8 digital dispute decisions, 10 Ombudsman reports, and also observations on three digital platforms, and finally, interviews with five informants, the research finds that the main reasons for disputes to arise are input errors, inaccurate cross-system verification, and the lack of digital objection channels. In contrast, most regulations do not include provisions on algorithmic transparency or system audit standards. The contribution and novelty of the study are linked to mapping the critical points of digital disputes and establishing a smart regulatory model that combines administrative law principles with automation mechanisms to increase the accountability of digital decisions, protect user rights, and improve the effectiveness of dispute resolution.